A Call for an Unbiased Search for Moderators in Disfluency Research: Reply to Oppenheimer and Alter (2014). Issue 5 (23rd April 2014) - Kühl, Tim; Eitel, Alexander; Scheiter, Katharina; Gerjets, Peter
Summary In a commentary to our article, Oppenheimer and Alter stressed the importance of searching for moderators in disfluency research. We agree, but we would like to clarify two issues. First, unlike Oppenheimer and Alter, we assume that learner characteristics might indeed moderate the effects of disfluency. Second, conclusions concerning the impact of disfluency in educational settings might be biased because of the file‐drawer problem. To counteract this possibility, we want to encourage other researchers to publish their studies––regardless of whether they found (positive) effects of disfluency or not. Until then, any recommendation concerning the use of disfluency as an educational intervention seems premature.